Students Perspective Toward E-Learning During Covid-19 At SMA Muhammadiyah Maumere In 2022/2023 School Year - Wea, Diniati; Rikardus Nasa; Nur Syamsiyah Ekhsan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
This study aims to analyze and describe students' perspectives on E-learning and the difficulties faced by students during online learning. Researcher use qualitative methods. Data collection techniques used in this study were observation, interviews by distributing questionnaires. From the results of an analysis of students' perspectives on online learning during the Covid-19 period, it was found that students felt that online learning made them quite bored and reduced interaction between teachers and students. Online learning also makes students less understanding of the material provided, so that it has an impact on the level of student focus. The difficulties faced by students in e-learning-based online learning are network access that is not power full, internet quota and facilities such as mobile phones do not yet exist. Based on the explanation above, the researcher concluded that students' perspectives on e-learning can reduce student learning levels and the ability to understand learning.